2020
DOI: 10.3390/polym12020301
|View full text |Cite
|
Sign up to set email alerts
|

Degradable Controlled Release Fertilizer Composite Prepared via Extrusion: Fabrication, Characterization, and Release Mechanisms

Abstract: In this work, biodegradable polymers were melt compounded with urea phosphate to fabricate “smart fertilizers” for sustainable agriculture. Urea phosphate (UP) is typically applied as a water-soluble fertilizer to treat phosphorus deficiency in high pH soils. Due to the low diffusion rate of phosphate through slow-release fertilizer coatings, phosphate supply has been considered the “bottleneck” for nitrogen–phosphorous–potassium (NPK) nutrients supply. We study the influence of polymer matrix structure on rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…Synthetic biodegradable aliphatic polyesters are hydrophilic and susceptible to hydrolytic degradation. This was confirmed by Ye et al [ 47 ] and Bi et al [ 48 ] by using different kinds of aliphatic polyesters as the coating material. These studies reported that increasing the size of coated fertilizer while using smaller crystals of urea dispersed in the matrix slows down degradation and the release rate.…”
Section: Coating Materialssupporting
confidence: 63%
“…Synthetic biodegradable aliphatic polyesters are hydrophilic and susceptible to hydrolytic degradation. This was confirmed by Ye et al [ 47 ] and Bi et al [ 48 ] by using different kinds of aliphatic polyesters as the coating material. These studies reported that increasing the size of coated fertilizer while using smaller crystals of urea dispersed in the matrix slows down degradation and the release rate.…”
Section: Coating Materialssupporting
confidence: 63%
“…In this line, Michalik and Wandzinc studied chitosan-based hydrogels [ 9 ]. On the other hand, different nutrients have been incorporated into bioplastic matrices, such as sodium and NPK (primary nutrients: nitrogen, phosphorus and potassium) [ 10 , 11 , 12 ]. There are also examples of controlled release of pesticides, such as the work of Singh et al [ 13 ], who used imidacloprid to release repellent odours for insects and microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…However, a steadily increasing demand for synthetic fertilisers has been observed over a few decades. The worldwide consumption of NPK fertilisers is expected to rise from 135.4 million tonnes (Mt) in 2000/2001 to 204 Mt in 2023/2024 [ 5 ]. Nevertheless, the fertilisation effectiveness remains comparatively low, which is caused by the fact that only 50–60% of N [ 5 , 6 ] and K and 10–25% of P are estimated to be utilised by cultivated plants [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The worldwide consumption of NPK fertilisers is expected to rise from 135.4 million tonnes (Mt) in 2000/2001 to 204 Mt in 2023/2024 [ 5 ]. Nevertheless, the fertilisation effectiveness remains comparatively low, which is caused by the fact that only 50–60% of N [ 5 , 6 ] and K and 10–25% of P are estimated to be utilised by cultivated plants [ 5 ]. Taking this into account, the global demand for N has been expected to reach 107 teragrams (Tg) N per year (with a limit of 50 Tg N reactive not absorbed by plants) by the year 2050 [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation